Assessing Physician Response Rate Using a Mixed-Mode Survey - Ahlers-Schmidt, Carolyn R; Chesser, Amy; Hart, Traci; Jones, Jordan; Williams, Katherine S; Wittler, Robert (Kansas Journal of Medicine, 2010)
Background. It is important to minimize time and cost of physician surveys while still achieving a reasonable response rate. Mixed-mode survey administration appears to improve response rates and decrease bias. A literature review revealed physician response rates to mixed-mode surveys averaged about 68%. However, no identified studies used the combination of e-mail, fax, and telephone. The purpose of this study was to evaluate physician response rates based on surveys first administered by e-mail, then fax, then telephone. Methods. Surveys initially were administered by e-mail to 149 physicians utilizing SurveyMonkey©. Two follow-up reminder e-mails were sent to non-respondents at two-week intervals. Surveys then were faxed to physicians who had not responded. A follow-up fax was sent to non-respondents one week later. Finally, phone interviews were attempted with physicians who had not responded by e-mail or fax; each physician was called at least twice. Results. Of the 149 eligible physicians, 102 completed the survey for a response rate of 68.5%. Of those who responded, 49 (48%) responded by e-mail, 25 (24.5%) by fax, and 28 (27.5%) by phone. Mode of response did not differ by gender, specialization, or years in practice. In addition, mode of response was not related to the primary study question, physician willingness to use text messaging for immunization reminders. Conclusions. This mix of survey methodologies appeared to be a feasible combination for achieving physician responses and may be more cost effective than other mixed methods.